Exploring School Principal Preparation and Development in Northern Canada: The Case of Nunavut's Educational Leadership Program (ELP) - Fredua-Kwarteng, Eric
The purpose of this research was to explore how Nunavut Educational Leadership (ELP), a school principal preparation program in Nunavut Territory, Canada, fulfills Inuit (the indigenous people of the territory) educational aspirations. In accordance with this purpose, the study focuses on answering four specific questions: (1) what are Inuit educational aspirations? (2) What is the context for Inuit education? (3) How is the Nunavut Educational Leadership Program organized to meet its objectives? (4) How do the activities of the Nunavut Educational Leadership Program (ELP) fulfill Inuit educational aspirations? Adopting an exploratory case study design grounded in qualitative approaches and undergirded by critical interpretative perspective, the research triangulates both primary and secondary sources of data. The primary data sources come from individual semi-structured interviews of 35 respondents (18 community members, 3 program development members, 3 presenters/facilitators, 7 program participants, and 4 educational officials) selected across Nunavut Territory. These sources are complemented with relevant secondary documents from 1987 to 2010. Using constant comparative and word-in-context as the main data analysis methods, concepts and themes were delineated from the data sources to form categories, with the research questions and conceptual framework guiding the process. The research results revealed, among many other things, that the Nunavut ELP partially fulfills Inuit educational aspirations as defined in the research. Issues arising from the data analysis and interpretation are also discussed under (1) Inuit culturally appropriate education/ self-determination in education, (2) Issues associated with Inuit and mainstream relationship, (3) The relationship between context and principal preparation and development programs, (4) Preparation programs for fulfilling local educational aspirations, (5) Framework for principal leadership practice, (6) Educational Governance Related-Issues, (7) University contribution to principal leadership preparation and development programs, (8) Nunavut ELP goals, and (9) Leadership Conceptualizations. Along with these are recommendations, theoretical implications and directions for future or further research. Though the research does not purport to design an educational leadership program for Nunavut school leaders, its evidence-based analysis and results may assist in any conversations toward the restructuring, improvement or enhancement of the Nunavut ELP as well as any educational leadership development programs in post-colonial societies. EDD